2009
DOI: 10.1039/b821169h
|View full text |Cite
|
Sign up to set email alerts
|

In situ generation of novel acyclic diaminocarbene–copper complex

Abstract: A novel acyclic diaminocarbene-copper complex appears to be generated from a chloroamidinium salt and Cu(I)-thiophenecarboxylate in the presence of Grignard reagent based on (13)C NMR studies and is a highly efficient catalyst for S(N)2'-allylic alkylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Compared to NHCs, ADCs typically possess wider N−C−N bond angles, are stronger σ-donors, and can be generated in a straightforward manner via deprotonation of readily accessible formamidinium salts . Furthermore, a broad range of metal complexes containing ADCs are known, some of which have been reported to be catalytically active . In addition to their unique electronic and steric properties, another remarkable aspect of ADCs is their structure.…”
mentioning
confidence: 99%
“…Compared to NHCs, ADCs typically possess wider N−C−N bond angles, are stronger σ-donors, and can be generated in a straightforward manner via deprotonation of readily accessible formamidinium salts . Furthermore, a broad range of metal complexes containing ADCs are known, some of which have been reported to be catalytically active . In addition to their unique electronic and steric properties, another remarkable aspect of ADCs is their structure.…”
mentioning
confidence: 99%
“…It has been previously reported that the interaction of a chiral imidazolium carbene silver(I) complex with CuCl 2 leads to the formation of a chloroamidinium salt. 12 In this report we have shown that this type of reaction is general for five-, six-, and sevenmembered ring diaminocarbenes. The exceptions are bidentate C Ÿ O chelating carbenes, for which the interaction of silver(I) complexes with CuCl 2 leads to the formation of the corresponding (NHC)Cu(II) complexes 1 3 and 5.…”
Section: Methodsmentioning
confidence: 66%
“…Accordingly, we were intrigued by the low cost as well as ease of handling of the related magnesium compounds. Inspiration came especially from two reports in the literature, in which the transmetalation of an anionic NHC ligand to iron [73] and of an acyclic diaminocarbene ligand to copper [78] was reported. In light of the recent report of heavy alkaline earth-NHC complexes embedded in tridentate coordination environments [79], we decided to explore the transmetalation from magnesium-NHCs in more detail.…”
Section: Introductionmentioning
confidence: 99%